2014
DOI: 10.1007/s12070-014-0794-3
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Dysphagia: Neurogenic Etiology and Manifestation

Abstract: To determine the type, severity and manifestation of dysphagia in patients with neurogenic etiology. Clinical documentation was done on the different etiologies, its manifestation, assessment findings and management strategies taken for patients with neurogenic oropharyngeal dysphagia who were referred for assessment and management of dysphagia over a period of three months in a tertiary care teaching hospital. Flexible endoscopic examination was done in all the patients. The severity of dysphagia in these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Prolonged oral or pharyngeal transit time 47 Piecemeal deglutition 47 Impaired secretion management e6…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Prolonged oral or pharyngeal transit time 47 Piecemeal deglutition 47 Impaired secretion management e6…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Across the included studies, the number of participants sampled per study ranged from 16 participants 20 to 486 participants 17 . Age related data was only reported by Sreeraj et al 17 (18 to 90 years) study, and the other studies 18-20 did not report any data with respect to age of the participants. Sex distribution of the participants was not clearly described in any of the four studies.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of identified dysphagia ranged from 11.1% 18 to 87.5%. 20 However, only two studies 17,19 reported occurrence of associated pneumonia. In Sreeraj et al 17 study, aspiration pneumonia was reported in 91 (22.8%) patients among 154 patients identified with dysphagia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations